Epistaxis as first manifestation of acute adult idiopathic thrombocytopenic purpura. Clinical case - Gómez-Torres, António (2013)
Idiopathic thrombocytopenic purpura (ITP) is a common hematologic disorder characterized by immune-mediated platelet destruction; it is usually a benign, self-limiting disease in children. The disorder typically presents with purpura and petechiae after viral processes of the upper airway. We report a case of a young man who came to the Emergency department with a very severe epistaxis. After nasal package of the nose, a full blood count showed no platelets. Case series of epistaxis always refer to hematologic disorder and treatment but it is very rare to find epistaxis as the first sign of ITP. ITP was diagnosed and treatment for the disease was instituted with a favorable response.